Central Obesity in Children and Adolescent: Current Themes and Future Potential Researches - Annang Giri Moelyo; Hanum Ferdian; Nanang Wiyono (Jurnal Kesehatan Masyarakat, 2025)
The increasing prevalence of central obesity among children and adolescents is a significant concern for public health, as it can lead to various health risks and complications. This study aimed to provide comprehensive updates using the keywords “central obesity,” and “children” or “adolescent”. The Scopus electronic database was searched for relevant articles to compile the basic publishing and citation data found in the article’s title, abstract, and keyword. The author, country, journal, and keyword networks were visualized using the bibliometric software program VOSviewer and biblioshiny. Of 1,190 articles, this study suggests the growth advancement with a 7.84% annual growth rate. The Plos One is the most international publication. The United States is the country leading in this topic. We find four theme clusters: obesity, central obesity, metabolic syndrome, and adolescents. The analysis shows that the diagnosis through anthropometric measurements, body fat assessment, metabolic syndrome, and complications were the major well-known research. The growing interest and future interest topics were waist-to-hip ratio, waist-to-height ratio, lifestyle, adiposity, and dyslipidemia. This bibliographic study showed the expanding publications of central obesity in children and adolescents and suggested several critical themes for future research.